2016
DOI: 10.1515/pjvs-2016-0102
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity of arcuate nucleus astrocytes in rats after intragastric administration of habanero peppers (Capsicum Chinese Jacq.)

Abstract: Habanero pepper fruits contain capsaicin (CAP) characterised by a spicy taste. Astrocytes express vanilloid receptor (TRPV1), which interacts with cannabinoids including CAP. Only a few studies revealed that CAP leads to alterations of the arcuate nucleus (ARC) structures. The aim of this study was to analyse the GFAP (GFAP-IR) and S100β (S100β-IR) immunoreactive astrocytes of ARC in adult rats after intragastric administration of habanero pepper fruits. Adult, Wistar rats received a peanut oil -control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A negative control for the primary antibody bypass reaction was performed simultaneously. In our earlier studies the specificity of the primary antibody was confirmed using the rat brain sections (24).…”
Section: Methodsmentioning
confidence: 74%
“…A negative control for the primary antibody bypass reaction was performed simultaneously. In our earlier studies the specificity of the primary antibody was confirmed using the rat brain sections (24).…”
Section: Methodsmentioning
confidence: 74%
“…CAP binds to neuronal receptors and astrocytic vanilloid 1 receptor (TRPV1). Some authors suggested that TRPV1 affects the synaptic plasticity in the hippocampal CA1 area [10][11][12][13]. Furthermore, it was found that the stimulation of TRPV1 receptor can lead to excessive activity of pyramidal neurons and the induction of seizures.…”
Section: Introductionmentioning
confidence: 99%